Utilizing U–Pb CA-TIMS dating to calibrate the Middle to Late Jurassic spore-pollen zonation of the Surat Basin, Australia to the geological time-scale. Issue 3 (3rd July 2018) - Wainman, C. C.; Hannaford, C.; Mantle, D.; McCabe, P. J.
Abstract : Wainman, C.C., Hannaford, C., Mantle, D. & Mc Cabe, P.J., April.2018. Utilizing U–Pb CA-TIMS dating to calibrate the Middle to Late Jurassic spore-pollen zonation of the Surat Basin, Australia to the geological time-scale. Alcheringa XX, xx-xx. Spore-pollen palynostratigraphy is commonly used to subdivide and correlate Jurassic continental successions in eastern Australia and thus aid the construction of geological models for the petroleum and coal industries. However, the current spore-pollen framework has only been tenuously calibrated to the geological time-scale. Age determinations are reliant on indirect correlations of ammonite and dinoflagellate assemblages from New Zealand, the North West Shelf of Australia and Southeast Asia to the standard European stages. New uranium-lead chemical abrasion thermal ionization mass spectrometry (U–Pb CA-TIMS) dates from 19 tuff beds in the Middle–Upper Jurassic Injune Creek Group of the Surat Basin enables regional spore-pollen palynostratigraphic zones to be precisely dated for the first time. These results show the base of the APJ4.2 and APJ4.3 subzones are similar in age to previous estimates (Middle Jurassic, Bathonian) from indirect palynostratigraphic correlation. However, the base of the APJ5 Zone and the APJ6.1 Subzone may be somewhat younger than previously estimated, possibly by as much as 2.5 and 4.2 Myrs, respectively. The continued utilization of U–Pb CA-TIMS dates will further refine the absolute ages of these zones, improve the inter- and intra-basinal correlation of Middle–Upper Jurassic strata in eastern Australian basins and greatly enhance intercontinental correlations. Carmine Christopher Wainman [ carmine.wainman@adelaide.edu.au ] and Peter James McCabe [ peter.mccabe@adelaide, edu.au ] Australian School of Petroleum, University of Adelaide, SA, 5005, Australia; Carey Hannaford [ carey.hannaford@mgpalaeo.com.au ] and Daniel Mantle [ dan.mantle@mgpalaeo.com.au ] MGPalaeo Pty Ltd, 5 Arvida Street, Malaga, WA, 6090, WA, Australia.